Odpowiedzi

2009-12-01T21:18:27+01:00
A) 2HNO3 + Mg(OH)2 -----> Mg(NO3)2 + 2H20
2H+ + 2NO3- + Mg2+ 2OH- ------> Mg2+ + 2NO3- + 2H20
2H+ + 2OH- ---------> 2 H20 /2
H + OH -------> H20

RESZTĘ ROBISZ PODOBNIE :)
Najlepsza Odpowiedź!
2009-12-01T21:49:49+01:00
A) 2HNO₃ + Mg(OH)₂ --->Mg(NO₃)₂ + 2H₂O
2H⁺ + 2NO₃⁻ + Mg²⁺ + 2OH⁻ ---> Mg²⁺ +2NO₃⁻ +2H₂O
2H⁺ + 2OH⁻ ---> 2H₂O

H₂CO₃ + 2KOH ---> K₂CO₃ +2H₂O
2H⁺ + CO₃²⁻ + 2K⁺ + 2OH⁻ ---> 2K⁺ + CO₃²⁻ + 2H₂O
2H⁺ + 2OH⁻ ---> 2H₂O

2H₃PO₃ + 3Fe(OH)₂ ----> Fe₃ (PO₃)₂ + 6H₂O
6H⁺ + 2PO₃⁻³ + 3Fe²⁺ + 6OH⁻ ---> 3Fe²⁺ + 2PO₃⁻³ +6H₂O
6H⁺ + 6OH⁻ ---> 6H₂O

3H₂SO₄ + 2Fe (OH)₃ --->Fe₂ (SO₄)₃ +6H₂O
6H⁺ + 3SO₄²⁻ + 2Fe³⁻ + 6OH⁻ ---> 2Fe³⁻ + 3SO₄²⁻ +6H₂O
6H⁺ + 6OH⁻ ---> 6H₂O

H₂S + 2NaOH ---> Na₂S + 2H₂O
2H⁺ + S²⁻ + 2Na⁺ + 2OH⁻ ---> 2Na⁺ + S²⁻ + 2H₂O
2H⁺ + 2OH⁻ --->2H₂O